MSME’s STRATEGY IN IMPROVING QUALITY DURING THE NEW NORMAL IN INDONESIA - Novalia, Diah Adinda; Devina, Dhea; Maya Panorama (CV. Era Digital Nusantara, 2022)
This study aims to identify and analyze strategies to improve the quality of MSMEs during the new normal which is affected by the Covid-19 pandemic. The research method used is descriptive qualitative method. The results obtained from this study indicate that there is a need for fast, precise and real steps from the government and business actors to cope with losses that have occurred due to the pandemic as well as utilize digital technology and follow the development of existing digital technology. such as promotions on social media and registering businesses to marketplace platforms, building personal branding, product innovation and diversification according to lifestyle.